Pelatihan Pembenihan Ikan Nila Pada Kolam Terpal Kepada Kelompok Pembudidaya Ikan Di Desa Sambora, Kecamatan Toho, Kabupaten Mempawah - Wira Hadinata, Fitra; Mulyadi, Achmad; Adijaya, Mardan (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
Sambora Village is one of the villages located in Toho District, Mempawah Regency. Sambora Village is inhabited by various tribes, ranging from Dayak, Malay, Madurese, Batak, Javanese, Bugis and Chinese. The activity partners in this PKM are the Sambora Village community, especially fish farmers and the public. Regarding the problems faced by partners, the solution is socialization and training regarding value fish hatcheries in tarpaulin ponds. The output target of this PKM activity is for partners to increase their knowledge and technical skills regarding fish hatcheries using tarpaulin ponds in their yards. The Community Service activities carried out consist of 3 stages, namely stage one is orientation, stage 2 is the implementation of socialization, and the last stage is monitoring and evaluation. At the orientation implementation stage, problems were found related to the need for fish seeds that grow quickly and are easy to adapt to the cultivation environment. The seeds used should come from quality brood stock and locally produced products. Socialization was carried out on the advantages of the fish hatchery method using tarpaulin ponds, comparisons were given with the hatchery method carried out in earthen ponds. Introduction to a type of tilapia fish that has good egg and sperm productivity. Implementation of monitoring and evaluation to provide input on seeding practices that have been carried out by partners and provide input regarding problems faced. After carrying out the three stages of PKM, the results showed that all training participants had increased their knowledge and abilities regarding tilapia fish hatchery. Before the training, 50% already had knowledge about tilapia fish hatcheries, but only 10% knew how to care for tilapia seeds in tarpaulin ponds. After socialization and training, all participants or 100% knew and were able to implement tilapia fish hatchery in tarpaulin ponds.